Variable dose rate application of herbicides using optical sensors - Antuniassi, Ulisses Rocha [UNESP] (2005)
The aim of this study was to develop and evaluate a variable dose rate application of herbicides using an online electronic control based system with optical sensors for weed detection in forested areas. The proposed concept was to apply a basic dose on 100% of the area (aiming to control small weeds) and to apply a complementary patch-spraying dose only on areas with higher weed infestation. For that purpose, a conventional spray boom was adjusted to apply 40% of the herbicide dose on the full area and the optical sensors were used to control the application of the complementary dose (60%) only on areas with higher infestation. The results showed that the system performed adequately. Field applications presented herbicide savings around 20 to 30%, with a similar weed control performance as compared to the full dose application on 100% of the area.